Weak smoking cessation awareness in primary health care before surgery: a real-world, retrospective cohort study - Gräsbeck H; Ekroos H; Halonen K; Vasankari T (TAYLOR & FRANCIS LTD, 2022)
Objective: Tobacco smoking is a well-established risk factor for postoperative complications. Research on preoperative smoking cessation in primary health care is scarce. Design: This was a retrospective cohort study. Setting: The Stop Smoking before Surgery Project (SSSP) started in Porvoo, Finland, in May of 2016, involving both primary health care and specialized health care. The goals of the project were smoking awareness and preoperative smoking cessation. Subjects: Our study involved 1482 surgical patients operated at Porvoo Hospital between May and December of 2016. Main outcome measures: We studied the recording of smoking status in all patients, and ICD-10 diagnosis of nicotine dependency and the initiation of preoperative smoking cessation in current smokers. Variables were studied from electronic patient records, comparing primary health care referrals and surgical outpatient clinic records. Results: Smoking status was visible in 14.2% of primary health care referrals, and in 18.4% of outpatient clinic records. Corresponding rates for current smokers (n = 275) were 0.0 and 8.7% for ICD-10 diagnosis of nicotine dependence, and 2.2 and 15.3% for initiation of preoperative smoking cessation. The differences between primary health care referrals and outpatient clinic records were statistically significant for all three variables (p <= .001). Conclusion: In primary health care, very little attention was paid to preoperative smoking cessation. Rates were significantly better at the surgical outpatient clinic, but still low. We could not demonstrate any certain effect of the intervention. Our results call for future research on ways to improve smoking cessation rates.